A New Social Contract for Peru : an Agenda for Improving Education, Health Care, and the Social Safety Net. - Cotlear, Daniel (World Bank country study., 2006)
"Using the accountability framework developed by the World Development Report 2004: Making Services Work for Poor People, this book analyzes the low-level equilibrium and the numerous reforms attempted in recent decades in Peru, and, based on this analysis, proposes interventions that would facilitate the creation of a new social contract for Peru."--Jacket.